Enhancing the device efficiency by filling the traps in photoanodes - Sudhakar, Vediappan; Krishnamoorthy, Kothandam (Journal of Materials Chemistry C, 2019)
Traps are ubiquitous in semiconductors and act as recombination sites. These recombination sites have a deleterious effect on the device efficiency. Thus, trap filling is used to increase the efficiency of devices. The traps are filled by dopants that either inject or extract electrons to/from the semiconductor. The trap-filled devices exhibit superior performance as compared to their unfilled counterparts. However, to date, this approach has not been explored in dye-sensitized solar cells despite the well-established presence of traps in them. The traps in the TiO2 photoanode are due to the presence of oxygen vacancies. Therefore, herein, we treated the photo anodes with hydrazine and filled the traps that increased all device metrics. Moreover, further sintering of the trap-filled photoanodes in the presence of hydrazine led to the formation of a nitrogen-doped photoanode. The device comprising a nitrogen-doped photoanode exhibited the efficiency increase of 23%. The detailed analysis of the device performance led to the conclusion that trap filling suppressed back electron transfer and increased the photo conversion efficiency.

Evolution of ZnO nanostructures as hexagonal disk: Implementation as photoanode material and efficiency enhancement in Al: ZnO based dye sensitized solar cells - Parra, Mohammad Ramzan; Pandey, Padmini; Siddiqui, Hafsa; Sudhakar, Vediappan; Krishnamoorthy, Kothandam; Haque, Fozia Z. (Applied Surface Science, 2019)
Hexagon shaped pristine and Al doped ZnO nanodisks (NDs) with exposed +/- [0001] polar facets were successfully synthesized using modified sol-gel method without the involvement of any structural directing or capping agents. It was investigated that OH- ions in mixed solvent system is responsible for pore formation and inhibit the growth of ZnO along the direction of c-axis leading to a high percentage exposure of active +/- [0001] polar facets and encourage the formation of ZnO NDs. Crystallographic analysis revealed that crystallite size and lattice constants are decreased, with the addition of Al3+ ions. The results obtained from Raman, and XPS analysis further corroborated with the XRD results, revealed the successful incorporation of Al3+ ions into ZnO lattice. Optical study revealed the band gap tunability with the incorporation of Al ion as dopant. Enhanced power conversion efficiency (PCE) of 1.96% (J(sc) similar to 7.69 +/- 0.23 mA/cm(2)) was observed for Al: ZnO hexagonal NDs based DSSC. The increased PCE in Al: ZnO based DSSC can be attributed to the higher inner surface area for dye anchoring by the interconnected network of the disk-like structure. The obtained results were satisfactory and most importantly the synthesis procedure proposed in present work is excellent for the synthesis of perfectly hexagonal shaped disks under precised synthesis parameters. The device interface study was further conducted using electrochemical impedance spectroscopy which revealed better charge transport process and charge storage ability with the incorporation of Al3+ ions into ZnO lattice.
Keywords: dye sensitized solar cells; Hexagonal disks; Sol-gel method; ZnO